UNDEFINITED AUTHORIZE CAPITAL IN COMPANY ESTABLISHMENT ACCORDING GOVERNMENT REGULATION NUMBER 29 YEAR 2016 RELATED OF “EAZY OF DOING BUSINESS” IN INDONESIA - Nur Hayati (Muhammadiyah Law Review Journal, 2017)
To expedite the development process and economic growth through investment, the Government has taken steps to increase of business in Indonesia. In consideration of the above-mentioned  points, it is necessary to change the authorized capital of a Limited Liability Company into an amount left to the discretion of the founders of a Limited Liability Company by agreement, on condition that the founders of a Limited Liability Company have net assets within the criteria for micro, small, and medium business. The government policy to give founders of a Limited Liability Company discretion to set the amount of authorized capital aims to increase investment as regulate by Government Regulation Number 29 of 2016. According hierarchy of law, government regulation lower than act, so the substance og government regulation can not contradictive with the substance of the act. This study will be analyze about the different of those regulation with Normative method. The major issue are finding answer about question “how about binding strength of government regulation number 29 of 2016 compare the act number 40 of 2007” and “how about legality of Company who establish according government regulation number 29 of 2016. Finally, we have conclusion that substance about authorize capital of regulation number 29 or 2016 is not conflict with act number 40 of 2007. We can look that as a discretion who made government to support the programe of “eazy of doing business” in Indonesia. Looking from hierarky of those regulation, although regulation number 29 or 2016 up down than act number 40 of 2007, that can make special rules as not conflict.